Bridging inequity gaps in healthcare through tailored support: implementation perspectives of the Social Health Bridge-Building Programme - Gitte Valentin; Thomas Maribo; Claus Vinther Nielsen; Merete Tonnesen; Lisa Gregersen Oestergaard (BMC Health Services Research)
Abstract Background Equity in access to and outcomes from healthcare is a fundamental pillar of universal healthcare systems. However, these systems have not eliminated social inequities in health. Significant socio-economic disparities persist in access to and utilisation of healthcare services, as well as in the quality and outcomes of care. The Social Health Bridge-Building Programme aims to enhance health equity by addressing multi-level barriers to healthcare. In this programme, healthcare student volunteers accompany individuals in a socially vulnerable situation to healthcare appointments, providing support before, during, and after these encounters. This reciprocal arrangement not only enhances the healthcare experience for the individuals involved but also offers student volunteers unique insights into the social determinants of health while fostering the development of essential communication skills. This study explores implementation perspectives of the programme, focusing on those accompanied to appointments. Methods Individuals accompanied to a healthcare appointment from August 2021 to June 2022 were asked to complete a web-based questionnaire covering socio-demographics, health literacy, physical and mental health, and satisfaction with the support provided. The frequency of accompaniments over six months were collected through telephone calls. Results A total of 187 users of the programme responded. The Individuals were characterised by short educational attainment, limited social support, unemployment, as well as poor physical and mental health. The majority reported difficulties comprehending health information and engaging with healthcare professionals. Forty percent of the accompaniments were to hospital visits and 23% to GP consultations, with most requesting multiple types of support such as emotional, transportation, communication, and way-finding. Most users (96%) reported that the student-volunteer accommodated their need for support. The additional number of accompaniments over six months ranged from 0 to 21. Conclusions The programme is successfully implemented for individuals in a socially vulnerable situation and succeeded in the delivery of a tailored programme that adresses the individuals’ specific needs and request. High satisfaction rates and the positive impact on healthcare experiences highlight the programme's potential to bridge existing inequity gaps in healthcare.